Stationary solution of heat-mass transfer problem in porous media with volumetrical heat source - Hai, Duong Ngoc (Vietnam Journal of Mechanics, 1988)
Process of electromagnetic heating and filtration of fluids in porous media with regard to mass transfer (melting or induration) is investigated. Theorem about existence and only stationary solution in dependence on geometrical characteristics of space, external heat action and thermal physical and electromagnetic characteristics of media has been proved. Regarded process is possibly used for drying and cleaning a porous media, for recovery and increased production of oils and etc.